2020
DOI: 10.1039/d0cp03161e
|View full text |Cite
|
Sign up to set email alerts
|

Solution combustion synthesis, characterization, magnetic, and dielectric properties of CoFe2O4 and Co0.5M0.5Fe2O4 (M = Mn, Ni, and Zn)

Abstract: Nanocrystalline CoFe2O4 and Co0.5M0.5Fe2O4 (M = Mn, Ni, and Zn) ferrites were prepared by solution combustion method using oxalyl dihydrazide as a fuel. These materials were characterized by several physicochemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…It is also observed that wavenumber corresponding to tetrahedral vibrations increases in the order FNP<ZNP<MNP<CNP respectively. The same trend has been observed in various reports [53]. This phenomenon particularly depends on the cation distribution, cation mass, and the ionic radii of the divalent cations.…”
Section: Fourier Transform Infrared Spectroscopy Analysissupporting
confidence: 88%
“…It is also observed that wavenumber corresponding to tetrahedral vibrations increases in the order FNP<ZNP<MNP<CNP respectively. The same trend has been observed in various reports [53]. This phenomenon particularly depends on the cation distribution, cation mass, and the ionic radii of the divalent cations.…”
Section: Fourier Transform Infrared Spectroscopy Analysissupporting
confidence: 88%
“…47 In general, the vibrational frequency of a bond is related to its force constant and the mass of the system. Classically, employing Hooke's law vibrational frequency ( n) in the wavenumber (cm À1 ) of a bond is expressed as: 30,44…”
Section: Ftir Spectroscopy Studiesmentioning
confidence: 99%
“…The choice of fuel is very important to determine the exothermicity of the redox reaction between the metal nitrate and fuel. 30 Within this context, it should be mentioned that based on the exothermicity of the reaction, the combustion is of different types such as flaming and smoldering. Flaming combustion begins with a high flame temperature, and an entire mass burns instantly leading to a fluffy mass and particles experience little sintering in the flame resulting in larger aggregated particles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3,4 ] The stunning multifunctional properties of ferrites such as large electrical resistivity and permeability, low eddy current, small dielectric loss, high saturation magnetization, etc., further extend its applications in magnetic data storage devices, transformer cores, antenna rods, etc. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…It can be used as a good candidate for data storage, magnetic storage, etc. [ 11 ] There are various reports in the scientific literature on the synthesis of Ni–Mg ferrites such as coprecipitation, [ 6,9 ] solid‐state reaction, [ 7 ] sol–gel method, [ 9 ] solution combustion, [ 5 ] citrate method, [ 12,13 ] etc. A simple and economically feasible synthesis technique which yields high‐quality nanoparticles opens further applications and development of ferrites.…”
Section: Introductionmentioning
confidence: 99%